Prevention of Chronic Morbidities in Extremely Premature Newborns with LISA-nCPAP Respiratory Therapy and Adjuvant Perinatal Strategies - Gergely Balázs; András Balajthy; István Seri; Thomas Hegyi; Tibor Ertl; Tamás Szabó; Tamás Röszer; Ágnes Papp; József Balla; Tamás Gáll; György Balla (MDPI AG, 2023)
Less invasive surfactant administration techniques, together with nasal continuous airway pressure (LISA-nCPAP) ventilation, an emerging noninvasive ventilation (NIV) technique in neonatology, are gaining more significance, even in extremely premature newborns (ELBW), under 27 weeks of gestational age. In this review, studies on LISA-nCPAP are compiled with an emphasis on short- and long-term morbidities associated with prematurity. Several perinatal preventative and therapeutic investigations are also discussed in order to start integrated therapies as numerous organ-saving techniques in addition to lung-protective ventilations. Two thirds of immature newborns can start their lives on NIV, and one third of them never need mechanical ventilation. With adjuvant intervention, these ratios are expected to be increased, resulting in better outcomes. Optimized cardiopulmonary transition, especially physiologic cord clamping, could have an additively beneficial effect on patient outcomes gained from NIV. Organ development and angiogenesis are strictly linked not only in the immature lung and retina, but also possibly in the kidney, and optimized interventions using angiogenic growth factors could lead to better morbidity-free survival. Corticosteroids, caffeine, insulin, thyroid hormones, antioxidants, N-acetylcysteine, and, moreover, the immunomodulatory components of mother's milk are also discussed as adjuvant treatments, since immature newborns deserve more complex neonatal interventions.